Genome-Wide Identification and Function Analyses of Heat Shock Transcription Factors in Potato - Tang, Ruimin; Zhu, Wenjiao; Song, Xiaoyan; Lin, Xingzhong; Cai, Jinghui; Wang, Man; Yang, Qing (Frontiers in Plant Science, 2016)
Heat shock transcription factors (Hsfs) play vital roles in the regulation of tolerance to various stresses in living organisms. To dissect the mechanisms of the Hsfs in potato adaptation to abiotic stresses, genome and transcriptome analyses of Hsf gene family were investigated in Solanum tuberosum L. Twenty-seven StHsf members were identified by bioinformatics and phylogenetic analyses and were classified into A, B and C groups according to their structural and phylogenetic features. StHsfs in the same class shared similar gene structures and conserved motifs. The chromosomal location analysis showed that 27 Hsfs were located in 10 of 12 chromosomes (except chromosome 1 and chromosome 5) and that 18 of these genes formed 9 paralogous pairs. Expression profiles of StHsfs in 12 different organs and tissues uncovered distinct spatial expression patterns of these genes and their potential roles in the process of growth and development. Promoter and quantitative real-time polymerase chain reaction (qRT-PCR) detections of StHsfs were conducted and demonstrated that these genes were all responsive to various stresses. StHsf004, StHsf007, StHsf009, StHsf014 and StHsf019 were constitutively expressed under non-stress conditions, and some specific Hsfs became the predominant Hsfs in response to different abiotic stresses, indicating their important and diverse regulatory roles in adverse conditions. A co-expression network between StHsfs and StHsf-co-expressed genes was generated based on the publicly-available potato transcriptomic databases and identified key candidate StHsfs for further functional studies.